THE EFFECT OF SERVICE PRICE SETTING ON PROFITABILITY IN PT PSIKOLOGI BAGI BANGSA BANDUNG - HASBI BASITH SUKARNO; Nursausan (POLITEKNIK PIKSI GANESHA, 2021)
This study has a goal to analyze the determination of the selling price of servicer to improve profitability in PT Psikologi Bagi Bangsa Bandung. The research method used is descriptive research method with quantitative approachment. Data analysis techniques used are normality test, correlation coefficient, coefficient of determination, simple linear regression analysis. Methods of data collection used by means of observation, interviews, literature review, and websites that have a close relevance to the subject matter. From the research conducted, it turns out the rise and fall of profit gained is influenced by the large or small selling price owned. It was proved by the results of correlation test conducted showed 0.939 results, meaning that the two variables in the test have a very close relationship. And obtained by result of linear regression analysis Y = 34097301,901 + 49,372X. The suggestion given by the researcher is Selling Price is important decision of company in strategy of increase its sale. It is advisable to the company, in addition to looking at market prices it should also be noted how the operating and investment costs are covered so as to produce a relatively steady and profitable return. Keywords: Selling price, Profitability.